An in situ small-angle X-ray scattering study of the structural effects of temperature and draw ratio of the hot-drawing process on ultra-high molecular weight polyethylene fibers. Issue 56 (25th May 2016) - An, Minfang; Xu, Haojun; Lv, You; Gu, Qun; Tian, Feng; Wang, Zongbao
Abstract : An in situ small-angle X-ray scattering study of the structural effects of temperature and draw ratio of the hot-drawing process on UHMWPE gel fibers was performed with equipment simulating the hot-drawing process on an industrial production line. Abstract : An in situ small-angle X-ray scattering (SAXS) study of the structural effects of temperature and draw ratio (DR1 ) of the hot-drawing process on ultra-high molecular weight polyethylene (UHMWPE) gel fibers was performed with equipment simulating the hot-drawing process on an industrial production line. The UHMWPE gel fibers were prepared from the industrial production line. The results show that the increase of hot-drawing temperature has a significant effect on the kebab but no obvious effect on shish length and misorientation. The increase of temperature is beneficial to the formation of the shish in a suitable temperature range of 124–130 °C, while the formation of the shish at higher temperature, 140 °C, needs higher DR1 . Moreover, the increase of DR1 is beneficial to the formation of shish at all experimental hot-drawing temperatures, while the kebab formation mainly occurs at low DR1 and the kebab transformation mainly happens at high DR1 . The shish length and misorientation decreases with the increase of DR1 .